Strategi Promosi Terhadap Objek Wisata Pura Mangkunegaran Di Surakarta - ., Sugiyarti (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
The problem in this research was how the perception of local community about Pura Mangkunegaran is habitat palace Sri Paduka Mangkunegara in Surakarta and built up by after year 1757 by following smaller keratin model,architecturely this building have characteristic which is equal to keraton, that is at Pamedan , Verandah of ancient palace, Pringgitan Dalem and Kaputren which is entirely encircled by sturdy wall.This research use descriptive method qualitative because have background to erudite paradigm, and existing data represent descriptive data in the form of oral data from behavior and people perceived or checked. Kuesioner which have spread over counted 200, but kuesioner which return counted 132 or equal to 66 %.Foreign countries tourist tend to take a fancy to Mangkunegara I struggle history/ Prince Sambernyawa in fight against Dutch,kesakralan access of night1 Suro, cultural artistry and attraction of Java. Nusantara tourist take a fancy to Kesakralan value in the form of intake water from event penjamasan of patrimony at night 1 Suro, special enthusiasm attraction in the form of night repast/ Prodigal of Dinner, cultural event in the form of event world heritage, commemoration of Pura Mangkunegaran anniversary, event Nuptials of Putra Princess, Some food and traditional snack performed by culinary tourism in Pura Mangkunegaran. In the tourism world specially part of marketing have to be brooding ever in striving promotion program morely effective, promotion strategy need to support executed promotion program effevtiveness. The effective promotion strategy is Above The Line and Below the Line. Above The Line Strategy which effective for the foreign countries tourist is through cultural event - event and Travel Book, while for the Nusantara tourist is through advertisement, baliho, product diversification in cinderamata market. Below The Line strategy which effective for the foreign countries tourist is through cultural attraction/traditional artistry and website/blog writing in internet Keywords : Strategy, Promotion, Tourism Destination